Managing epidemics : key facts about major deadly diseases - Prentice, Thomson; Bradd, Sam (World Health Organization, 2018)
This manual provides concise and up-to-date knowledge on 15 infectious diseases that have the potential to become international threats and tips on how to respond to each of them. The 21st century has already been marked by major epidemics. Old diseases - cholera the plague and yellow fever - have returned and new ones have emerged - SARS pandemic influenza MERS Ebola and Zika. These epidemics and their impact on global public health have convinced the world s governments of the need for a collective and coordinated defense against emerging public health threats and accelerated the revision of. Nakladatelská anotace.
WHO handbook
Keywords: Communicable Diseases; Primary Prevention; Communicable Disease Control; Global Health; celosvětové zdraví; Risk Management; veřejné zdravotnictví; epidemický výskyt choroby; epidemie; Disease Outbreaks; preventivní medicína; kontrola infekčních nemocí; řízení rizik; infekční nemoci; epidemiologie; primární prevence; Epidemics